Bilateral Total Knee Arthroplasty: Challenges and Need for Follow-up - Subramanian, S. S. (Medical Science: Trends and Innovations Vol. 2, 2025)
Osteoarthrosis of knee joint, major indication for total knee replacement (TKR). TKR was one of the most elective operations globally. Multiple factors including Obesity, and preoperative lumbar spine disorders influence post-TKR outcomes. Lifelong follow-ups are required to combat falls, low back ache, obesity, chronic pain, and functional activities for post-TKR. 10 years post-TKR subject developing low back ache was getting treated for 2 years with specific advanced patient-centric physiotherapeutic means. The results of this non-pharmacological therapy were discussed with evidence. The findings of this presentation insist on longitudinal, lifelong follow-up of health care experts, and better living of post-TKR subjects.